AN ANALYSIS OF METAPHOR AND SIMILE TRANSLATION STRATEGIES IN “THE JUNGLE BOOK” NOVEL - Harun Sigit; Silvia Erlin Aditya Sembiring (UNIVED Press, 2020)
This study examined about metaphor and simile translation strategies in “The Jungle Book